Cu2O nanocrystals: Unveiling facet-dependent catalysis in phenylacetylene homocoupling - Satyaranjan Jena; Arnab Ghosh; Novuhulu Rhakho; Ramesh B. Dateer; Akshaya K. Samal (Sustainable Chemistry for the Environment)
We report a one-pot synthesis method to synthesize Cu2O nanocubes (NCs) and octahedra (Oh) using mild reducing agents such as ascorbic acid (L-AA), and D-glucose, respectively. The shape-dependent nanostructures of Cu2O have been characterized using various spectroscopic and microscopic techniques exhibiting an average size of 450 and 650 nm for Cu2O NCs and Oh, respectively which is influenced by their size and presence of various facets. X-ray diffraction (XRD) patterns reveal the crystalline nature of Cu2O nanostructures. The synthesized Cu2O NCs and Oh were investigated for their catalytic potential in phenylacetylene homocoupling organic reaction. The aryl alkyne homocoupling reaction demonstrates excellent efficacy under optimized reaction conditions. This work highlights the potential of (111)-bound Cu2O Oh in achieving high organocatalytic activity for aryl alkyne homocoupling transformations. Furthermore, Cu2O Oh demonstrated efficacy in catalyzing a wide range of substituted aryl alkynes under optimized reaction conditions, underscoring the importance of facet engineering in nanocatalysts for organic coupling reactions. The study found that Cu2O Oh exhibited enhanced catalytic efficiency, achieving a yield of 95.6 %, which is significantly higher than the 54.3 % yield obtained with Cu2O NCs. This superior performance of Cu2O Oh is attributed to the high catalytic activity of the (111) facets.